Evaluasi Pemanfaatan Aplikasi e-PPGBM untuk Entri Data Gizi di Kabupaten Timor Tengah Selatan, Indonesia: Hasil Penelitian - Tanesab, Delto Loisandro; Ully, Yuniar Dumaria (PT Kalbe Farma Tbk., 2026)
Introduction: Management of stunting problems in South Central Timor Regency needs effective health information system, particularly the Electronic-Community-Based Nutrition Recording and Reporting (e-PPGBM) application. This study aims to describe patterns of data entry delays and identify factors that are believed to contribute to data entry delays. Methods: Secondary data analysis based on reports from the South Central Timor Regency Health Office, supplemented with online interviews through the Zoom platform to explore the reasons behind data entry delays. Results: Among the 37 primary health centers, 27 recorded data for the IKG indicator in January, 11 in February, and none in March. For the National Medium-Term Development Plan (RPJMN) indicator, 23 centers entered data in January, 5 in February, and nonein March. The delays were mainly attributed to limited human resources, lack of supervision, and technical difficulties in using the application. Conclusion: Increased supervision, adequate equipment, and continuous assistance from the Health Office are needed to improve the accuracy of data entry. Regular evaluation is expected to improve the effectiveness of e-PPGBM in supporting nutrition interventions in South Central Timor District.